Effect of Leaf Age on the Insecticidal Activity of Mahogany (Swietenia mahagoni Jacq.) Leaf Extract Against Setora nitens Walker - Idum Satia Santi; Emmy Hamidah; Agus Manto; Indra Kurniawan; Theofilus Tejo Murti (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Setora nitens Walker is an important defoliating pest in oil palm plantations. Botanical insecticides offer an environmentally friendly alternative to synthetic pesticides for pest management. This study evaluated the influence of leaf age and concentration of mahogany (Swietenia mahagoni Jacq.) leaf extract on the mortality of S. nitens larvae. Young and mature mahogany leaves were extracted using water and applied to oil palm leaflets through a spraying method. Four extract concentrations (30%, 40%, 50%, and 60%) and an untreated control were tested. Larval mortality was observed for seven days after treatment. All extract treatments increased larval mortality compared with the control. The highest average mortality (83.8%) was recorded in the 50% concentration of young leaf extract, while the lowest mortality (69.5%) occurred in the 30% concentration of young leaves and the 40% concentration of mature leaves. All extract treatments resulted in 100% cumulative mortality by the end of the observation period, whereas no mortality was observed in the control. Young leaf extracts generally produced higher mortality than mature leaf extracts. These findings indicate that mahogany leaf extract has potential as a botanical insecticide against S. nitens. The higher effectiveness of young leaf extracts suggests that leaf age influences the insecticidal activity of mahogany leaves.